Sexually transmitted infections in Morocco: acceptance of expedited partner therapy in a context of social vulnerability - Nezha NACER, Nadia OUZENNOU, Jaouad CHOUIKH and Samia RKHA (South Eastern European Journal of Public Health, 2025)
Background and objectives: Untreated partners contribute to high rates of reinfection with sexually transmitted infections. Partner treatment, therefore, remains an important element in the treatment and control of these infections. In this context, the present study aims to investigate the acceptability, for women of childbearing age, of expedited partner treatment in the presence of a sexually transmitted infection syndrome and to determine the associated factors. Methods: This is a descriptive and analytical cross-sectional study. The study was conducted in urban and rural health centers in the province of Essaouira, Morocco. All women of childbearing age who consulted the health centers and agreed to complete the questionnaire were recruited. A questionnaire was used to study respondents' acceptance of partner treatment in the presence of a sexually transmitted infection syndrome. Univariate and multivariate statistical analyses were performed. Finding: A total of 1100 women of reproductive age participated in the study. The average age of the respondents was 30.6 years ± 8. In total, 53.5% of respondents said they would agree to give their partner expedited therapy to the partner. The multivariate analysis found that the acceptability of expedited therapy is correlated with marital status, distance to care facilities, educational level, and socio-economic level according to household income. Conclusions: More than half of the 1100 women of childbearing age surveyed accepted the idea of expided partner therapy. In this sense, the implementation of partner support strategies, including education and outreach programs, should be considered to anchor preventive behaviors related to these infections.